Intravenous digital subtraction angiography in the diagnosis of brain death. - Gomes, A S; Hallinan, J M (American Journal of Neuroradiology, 1983)
The diagnosis of brain death requires: (1) the performance of all appropriate and therapeutic procedures; (2) the presence of cerebral unresponsivity, apnea, dilated pupils, absent cephalic reflexes, and electrocerebral silence; and (3) if one of these criteria cannot be tested or is met imprecisely, the performance of a confirmatory test to demonstrate the absence of cerebral blood flow. Selective cerebral arteriography has been the most widely used method of assessing cerebral blood flow. Digital intravenous angiography was used as a means of evaluating cerebral blood flow, and it was found to be a useful confirmatory test in the diagnosis of brain death.